Corruption and oil exploration: expert agreement about the prevention of HIV/AIDS in the Niger Delta of Nigeria - Udoh, Isidore A. (Oxford University Press, 2008)
The Niger Delta, according to the Nigerian Ministry of Health, has a disproportionately high HIV infection rate, which is double the national average. The United Nations Development Program attributes the spiraling HIV infection rate in the region to poverty, migration and gender inequality. This paper examines two complementary suppositions: Is the high prevalence of HIV in the Niger Delta related to incompetent leadership and corruption? Is it related to the negative effects of oil exploration in the region? Currently, there is a dearth of research on the effectiveness of government programs or the role of the oil industry on the impact of AIDS in Nigeria. To address this gap, we conducted a survey with 27 internationally renowned experts from diverse disciplines using a three-round modified Delphi to formulate consensus about the impact of weak governance and oil corruption on AIDS in the Niger Delta. Results from the Delphi suggest that these factors and others have exacerbated the transmission of HIV in the region. To mitigate the impact of AIDS in the region, efforts to engage oil companies in implementing HIV prevention programs as part of their corporate environmental responsibility to the community are urgently needed.